Ex-ante benefit-cost analysis of the elimination of a Glossina palpalis gambiensis population in the Niayes of Senegal. - Fanny Bouyer; Momar Talla Seck; Ahmadou H Dicko; Baba Sall; Mbargou Lo; Marc J B Vreysen; Eduardo Chia; Jérémy Bouyer; Abdrahmane Wane (Public Library of Science (PLoS), 2014)
In 2005, the Government of Senegal embarked on a campaign to eliminate a Glossina palpalis gambiensis population from the Niayes area (∼ 1000 km(2)) under the umbrella of the Pan African Tsetse and Trypanosomosis Eradication Campaign (PATTEC). The project was considered an ecologically sound approach to intensify cattle production. The elimination strategy includes a suppression phase using insecticide impregnated targets and cattle, and an elimination phase using the sterile insect technique, necessary to eliminate tsetse in this area.Three main cattle farming systems were identified: a traditional system using trypanotolerant cattle and two "improved" systems using more productive cattle breeds focusing on milk and meat production. In improved farming systems herd size was 45% lower and annual cattle sales were €250 (s.d. 513) per head as compared to €74 (s.d. 38) per head in traditional farming systems (p<10-3). Tsetse distribution significantly impacted the occurrence of these farming systems (p = 0.001), with 34% (s.d. 4%) and 6% (s.d. 4%) of improved systems in the tsetse-free and tsetse-infested areas, respectively. We calculated the potential increases of cattle sales as a result of tsetse elimination considering two scenarios, i.e. a conservative scenario with a 2% annual replacement rate from traditional to improved systems after elimination, and a more realistic scenario with an increased replacement rate of 10% five years after elimination. The final annual increase of cattle sales was estimated at ∼ €2800/km(2) for a total cost of the elimination campaign reaching ∼ €6400/km(2).Despite its high cost, the benefit-cost analysis indicated that the project was highly cost-effective, with Internal Rates of Return (IRR) of 9.8% and 19.1% and payback periods of 18 and 13 years for the two scenarios, respectively. In addition to an increase in farmers' income, the benefits of tsetse elimination include a reduction of grazing pressure on the ecosystems.